Putin’s Russia in Der Spiegel’s Journalism - Fuchs, Klaus (Respectus Philologicus, 2003)
The paper investigates the weekly journal DER SPIEGEL’s – one of Germany’s most influential media – image of Russia as a subject of foreign policy and as a society at the beginning of the Putin era. It thus further elaborates on the author’s short text in Respectus Philologicus 3 (8) / 2003. A comprehensive quantitative and qualitative analysis of DER SPIEGEL’s Russia-related topics is presented, the purpose of which is to illustrate German public opinion’s ideas and stereotypes on Russia as reflected by one of German society’s most successful media.